2019
DOI: 10.1038/s41467-019-09504-3
|View full text |Cite
|
Sign up to set email alerts
|

Anion-adaptive crystalline cationic material for 99TcO4− trapping

Abstract: Efficient anion recognition is of great significance for radioactive 99 TcO 4 − decontamination, but it remains a challenge for traditional sorbents. Herein, we put forward a tactic using soft crystalline cationic material with anion-adaptive dynamics for 99 TcO 4 − sequestration. A cucurbit[8]uril-based supramolecular metal-organic material is produced through a multi-component assembly strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 74 publications
1
42
0
1
Order By: Relevance
“…These recent findings open a very attractive avenue for MOF applications for environmental remediation of various contaminants (Mon et al, 2018) and nuclear waste treatment (Banerjee et al, 2016b;Dolgopolova et al, 2018). More recently, several MOFs (Banerjee et al, 2016a;Banerjee et al, 2016c;Drout et al, 2018;Fei et al, 2011;Li et al, 2017b;Mei et al, 2019;Rapti et al, 2018;Sheng et al, 2019;Sheng et al, 2017;Xu et al, 2019;Zhu et al, 2017a) and cationic organic framework (Da et al, 2019;Ding et al, 2020;He et al, 2019;Li et al, 2018;Liu and Han, 2020;Samanta et al, 2018;Shen et al, 2017;Sun et al, 2019;Zhu et al, 2017b) have demonstrated the ability to trap ReO 4 − from aqueous media.…”
Section: Introductionmentioning
confidence: 95%
“…These recent findings open a very attractive avenue for MOF applications for environmental remediation of various contaminants (Mon et al, 2018) and nuclear waste treatment (Banerjee et al, 2016b;Dolgopolova et al, 2018). More recently, several MOFs (Banerjee et al, 2016a;Banerjee et al, 2016c;Drout et al, 2018;Fei et al, 2011;Li et al, 2017b;Mei et al, 2019;Rapti et al, 2018;Sheng et al, 2019;Sheng et al, 2017;Xu et al, 2019;Zhu et al, 2017a) and cationic organic framework (Da et al, 2019;Ding et al, 2020;He et al, 2019;Li et al, 2018;Liu and Han, 2020;Samanta et al, 2018;Shen et al, 2017;Sun et al, 2019;Zhu et al, 2017b) have demonstrated the ability to trap ReO 4 − from aqueous media.…”
Section: Introductionmentioning
confidence: 95%
“…55 4B). 56 The authors noted that commercially available ll cucurbituril macrocycles have outwardly pointing CH hydrogen-bond donors that could be utilized for anion recognition upon self-assembly of the macrocycles. They synthesized a 3D supramolecular framework by mixing cucurbit [8] , because of the hydrophobic nature of CH donors.…”
Section: Llmentioning
confidence: 99%
“… 30 , 31 As an emerging candidate to sequester TcO 4 – from nuclear waste, metal–organic frameworks (MOFs) are endowed with the unique advantages of tailored porous structures and facile functionalization, relying on their modular building blocks. 32 35 Some cationic MOFs exhibit good sorption capability and selectivity to pertechnetate, but slow kinetics, low stability, and poor recyclability under highly acidic conditions. 36 38 …”
Section: Introductionmentioning
confidence: 99%